Projecting the Learning Attainment of Speech and Hearing Impairment Students from Domestic, Discrete, Communication and Educational Aspects - Karthigadevi, K.; Thangarasu, S. (Journal of Engineering Education Transformations, 2021)
It is the responsibility of any educational institution to cater to the learning accomplishment of the speech and hearing-impaired students. These factors contain experiences inside and outside the college (grade maintenance), environmental characteristics of the family (economic status, level of education of parents), and the students’ characteristics such as fluency of language, way of communication, communication functioning and hearing thresholds). This paper looks at the significance of such characteristics to develop academic competence in mathematics, computer science and social studies. Two different groups of students from speech and hearing-impaired college as well as those from higher secondary schools are analyzed. The study showed that the speech and hearing-impaired students are eager to continue their higher education. Particularly if they are provided with the right tools, the majority of these students are keen on studying computer science. The conclusions derived about the status of disability of the student and the implementation supports of teacher on goal attainment outcomes are analyzed.